Neuroplasticity: The MIT Essential Knowledge Series (Academic Journal of Internal Affairs, 2021)
As editor Bruce Tidor sets it in the preface of the book, published in the volume of the MIT Essential Knowledge series: ‘Synthesizing specialized subject matter for non-specialists and engaging critical topics through fundamentals, each of these compact volumes offers readers a point of access to complex ideas.’ (Costandi, 2016). In this book of the series Moheb Costandi provides the reader with a celar and coherent picture about neuroplasticity and neurogenesis . Not just at the level of theories and research results, but also regarding various stages of practical application. It is equally applicable for average people in areas of everyday life- adult education, lifelong learning, and mental training, too. Costandi’s book is decidedly good background material for Anders Hansen’s practical book ‘The Real Happy Pill: Power Up Your Brain by Moving Your Body’ (Németh, 2020).
Keywords: lifelong learning; adult education; neuroplasticity; neurogenesis